5-Hydroxymethylcytosine profilings in circulating cell-free DNA as diagnostic biomarkers for DLBCL - Chen, Hangyu; Duolikun, Maimaitiyasen; Zhu, Hai-Chuan (Frontiers in Cell and Developmental Biology, 2024)
Background 5-Hydroxymethylcytosine (5hmC) is an important DNA epigenetic modification that plays a vital role in tumorigenesis, progression and prognosis. Previous studies have shown that it plays an important role in the prognosis of diffuse large B-cell lymphoma (DLBCL) and in the prediction of the efficacy of R-CHOP therapy. However, its potential for diagnosing DLBCL has not been reported. Here, we investigated the utility of 5hmC in plasma cfDNA in the diagnosis of DLBCL. Methods Applying 5hmC-Seal technique, we obtained genome-wide 5hmC profiles in plasma cell-free DNA (cfDNA) samples from 176 Chinese subjects, included 86 DLBCL patients and 90 healthy controls. To investigate whether 5hmC can be used as a diagnostic biomarker for DLBCL, we separated patients and healthy controls into training (DLBCL = 56, Healthy = 60) and validation (DLBCL = 30, Healthy = 30) cohorts and developed a 5hmC-based logistic regression model from the training cohort to diagnose the DLBCL patients in the validation cohort. Results In this study, we found 10 5hmC biomarkers, and the models created by these differentially regulated 5hmC modified genes showed high accuracy in distinguishing DLBCL patients from healthy controls (validation cohort: AUC = 0.94; (95% CI 88.8%–99.4%)). Conclusion Our study suggested that 5hmC markers derived from plasma cfDNA can served as effective epigenetic biomarkers for minimally invasive diagnosis of DLBCL.